SOCIO-ECONOMIC ANALYSIS OF BEEKEEPING AND DETERMINANTS OF BOX HIVE TECHNOLOGY ADOPTION IN THE KINGDOM OF SAUDI ARABIA - N. Adgaba; A. Al-Ghamdi; A. G. Shenkute; S. Ismaiel; S. Al-Kahtani; Y. Tadess; M. J. Ansari; W. Abebe; M. Q. A. Abdulaziz (Journal of Animal and Plant Sciences, 2014)
Despite the extensive beekeeping practices in Saudi Arabia, relevant information related to socio-economic profiles of beekeeping and factors affecting the adoption of improved beekeeping technologies were lacking. To understand these conditions, 182 beekeepers from five regions were interviewed using exhaustive questionnaires and the data were analyzed using descriptive statistics and logistic model. The study revealed that still 71.1% of the honeybee colonies in the country are kept in traditional hives and the adoption of box hives have been observed to be significantly influenced by the beekeeper’s socio-demographic profiles. Education level had positively influenced the adoption of box hive, which could be due to the fact that education increases knowledge, accesses to information and easily understanding of the technology. The less acceptance of box hive was also implicated with its unsuitability to the biology and ecology of the local bees, which may indicate lack of consideration of these factors in selection and adoption of the technology. The majority (71.5%) of the respondents keep local bees for their better adaptability and 82% of the imported hybrid bees reported to die after one honey-harvesting which could be due to lack of adjustment to the new environment as result of the residual effect of the behavioral rhythms of their original homeland. The majority (93%) of beekeepers reported to migrate their colonies 2-9 times per annum which is important to exploit resources available at different seasons and ecologies. The average annual productivities of colonies were 6.64±5.64kg and 3.69±2.62 kg honey/colony/annum for box and traditional hives, respectively. The average price of locally produced honey is high and varies from $58.87 to $77.86/kg and this has contributed to attract and sustain many people in the beekeeping business. The average annual household earnings from beekeeping was relatively high ($58,937.6), and contributes to an average of 29.67 ±28.95% of the total annual income of beekeepers which show that beekeeping plays a significant role in increasing and diversifying the incomes of rural communities. The major constraints of beekeeping in the country as outlined by beekeepers are absence of rain, shortage of bee forage and honey bee enemies. To enhance the development of the subsector: a strong extension and research supports; consideration of the biology and ecology of the local race in selection and adoption of beekeeping technologies; focusing on conservation and rehabilitation of vegetation with integration of beekeeping; establishing of colony multiplication center and conserving of the indigenous honeybee race would be very important.
Keywords: beekeeping; socio-economic; box hive; adoption; honey production; Apismelliferajemenetica; Saudi Arabia